Administration of I.V. lidocaine before induction of general anesthesia prolong suxamethonium action in caesarian section surgeries. clinical assessment-------- - layla Khalil (مجله كليه طب الكندي, 2019)
Background: Known as suxamethonium or succinylcholine, is a medication used to cause short-term paralysis as part of general anesthesia. The duration of operation is one of the important factors accounting to the success of the operation. Simple safe available drug can change the plan of anesthesia.